Pengaruh Kegiatan Pasir Kinetik Terhadap Kemampuan Motorik Halus Anak Usia 4-5 Tahun - H. Abu, Sri Pati; Jamin, Nunung Suryana; Juniarti, Yenti; Sumirat, Elva M (Jambura Early Childhood Education Journal, 2024)
The problem addressed in this research is whether kinetic sand activities affect the fine motor skills of early childhood children aged 4-5 years at TK Melati Kindergarten, Gonggong Village, Banggai Laut Regency. This research aims to determine the effect of kinetic sand activities on the fine motor skills of early childhood children aged 4-5 years. This research is a quantitative study with control and experimental classes at TK Melati Kindergarten, Gonggong Village, Banggai Laut Regency, involving a total of 16 children. Data analysis was performed using statistical data processing. The results showed an increase in the average pre-test score, with a mean of 14.8 and a standard deviation of 2.47. The post-test data showed a mean score of 25.6 and a standard deviation of 3.00. This indicates that the respondents showed average improvement from the initial to final tests. From the significant test results, the tcount = 17.2 while the ttable value at (α) = 0.05 is 0.2 if tcount> ttable; 17.2> 0.2. Thus, H1 is accepted, and H0 is rejected. If tcount> ttable, it means that Kinetic Sand Activities affect the fine motor skills of early childhood 4-5 years at TK Melati Kindergarten, Gonggong Village, Banggai Laut Regency.